2019
DOI: 10.1002/jcb.29109
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of dopaminergic signaling by Pitx3–GDNF synergy induces dopamine secretion by multipotent Ntera2 cells

Abstract: Human teratocarcinoma cell line Ntera2 (NT2) expresses dopamine signals and has shown its safe profile for clinical applications. Attempts to restore complete dopaminergic (DAergic) phenotype enabling these cells to secrete dopamine have not been fully successful so far. We applied a blend of gene transfer techniques and a defined medium to convert NT2 cells to fully DAergic. The cells were primarily engineered to overexpress the Pitx3 gene product and then cultured in a growth medium supplemented with knockou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
(152 reference statements)
0
4
0
Order By: Relevance
“…In general, there are several potential cell types, including human teratocarcinoma cell line Ntera2, neural stem cells, iPS cells, ES cells, MSCs, olfactory ecto‐MSCs (OE‐MSCs), and somatic cells, which could directly convert into DA neuron‐like cells (Alizadeh et al, ; Alizadeh et al, ; Alizadeh et al, ; Björklund et al, ; Choi et al, ; Eskandarian Boroujeni, Aliaghaei, Maghsoudi, & Gardaneh, ; Lindvall et al, ; Roy et al, ). For instance, Alizadeh, Kamrava, et al () used a new source of MSCs, human OE‐MSCs derived from the adult human olfactory mucosa, and differentiated these cells into DA‐neuron cells successfully by factors such as bFGF, SHH, FGF8, GDNF, and BDNF in 12 days.…”
Section: Discussionmentioning
confidence: 99%
“…In general, there are several potential cell types, including human teratocarcinoma cell line Ntera2, neural stem cells, iPS cells, ES cells, MSCs, olfactory ecto‐MSCs (OE‐MSCs), and somatic cells, which could directly convert into DA neuron‐like cells (Alizadeh et al, ; Alizadeh et al, ; Alizadeh et al, ; Björklund et al, ; Choi et al, ; Eskandarian Boroujeni, Aliaghaei, Maghsoudi, & Gardaneh, ; Lindvall et al, ; Roy et al, ). For instance, Alizadeh, Kamrava, et al () used a new source of MSCs, human OE‐MSCs derived from the adult human olfactory mucosa, and differentiated these cells into DA‐neuron cells successfully by factors such as bFGF, SHH, FGF8, GDNF, and BDNF in 12 days.…”
Section: Discussionmentioning
confidence: 99%
“…Another well-known and essential partner of the NURR1 is the homeobox transcription factor PITX3 (Table 1) [73,82]. NURR1 alone cannot drive the DAergic phenotype in meso-diencephalic DAergic neurons, due to co-repression by PSF (SFPQ; PTB-associated splicing factor) and SMRT (silencing mediator of retinoic acid and thyroid hormone receptor), that can interact with NURR1 and occupy its promoters target genes (Figure 2).…”
Section: Regulation Of Nurr1 Activity By Protein-protein Interactionsmentioning
confidence: 99%
“…Hence, PITX3 is essential for the transcriptional activity of NURR1, activating its function through its response elements and allowing the development of the DAergic phenotype. This mechanism provides new insights underlying the development of midbrain DAergic neurons and stem cell reprogramming as future therapies for PD [82]. p57Kip2 (cyclin-dependent kinase inhibitor 1C (CDKN1C)) is another protein th makes heterodimers with NURR1 and is essential for normal DAergic neuron develo ment (Table 1) [74].…”
Section: Regulation Of Nurr1 Activity By Protein-protein Interactionsmentioning
confidence: 99%
“…NT2derived neuron-like cells can give rise to the growth of axons and dendrites [98]. Thus, NT2 cells have long been thought of as a replacement source of mDA neurons for PD cell treatment [99]. Recent studies showed that after overexpressing Pitx3 and being exposed to GDNF, NT2 cells could release DA, indicating that Pitx3-GDNF interactions in DA signaling may promote the dopaminergic neuronal properties of NT2 cells, making it clinically applicable for cell replacement therapy in PD [99].…”
Section: The Role Of Pitx3 In Cell Therapymentioning
confidence: 99%